Predictive Value of Haematological Indices on Mortality in Patients with Empyema - Celik, Ali Kutta; Ali SALAD, Abdikani; zortuk, ökkeş (Journal of Medical Biochemistry, 2025)
Background:Empyema is an infectious disease characterized by the accumulation of pus in the pleural space and accompanied by inflammation. Patients often present with fever, chest pain, dyspnea, or cough, and delayed diagnosis or treatment is associated with high mortality rates. Therefore, in this study, we aim to investigate the clinical utility of the Systemic Inflammation Response Index (SIRI), Pan-Immune Value (PIV), C-Reactive Protein (CRP)-Albumin-Lymphocyte (CALLY) index, and Systemic Immune-Inflammation Index (SII) in assessing the severity of empyema and predicting mortality risk.Methods:Between January 2022 and October 2024, 73 patients diagnosed with empyema in the thoracic surgery clinic were included in the study. Patients were categorized based on the need for intensive care. Demographic and laboratory data (e.g., white blood cell count, platelet count, albumin levels, pleural fluid culture results, and C-reactive protein levels) were recorded. Differences between empyema patient groups, classified according to disease severity, were analyzed.Results:Among the 73 patients included in our study, 4 deaths were recorded. It was observed that the CALLY index could be used for intensive care and ward triage (p:0.039). While the SII and SIRI indices were not suitable for triage purposes, the SIRI index was found to be useful for predicting mortality (p:0.01).Conclusion:In empyema cases, the CALLY index can be used to determine the need for intensive care, while the SIRI index can help predict mortality risk.
Keywords: empyema severity, biomarker, CALLY, SII, SIRI, PIV